Environmental and economic potential of high-capacity trucks - Solakivi, Tomi; Ojala, Lauri (Elsevier, 2025)
High-capacity trucks (HCTs) are vehicles that are heavier or larger than normally allowed and are used as a means of increasing the efficiency of road freight transport and reducing emissions.
The present research analyses the economic and environmental efficiency of HCTs by comparing them with normal semitrailers. Survey-based estimates on cost structure, fuel consumption, load factor and empty running of semitrailers, road trains and HCT combinations currently operating in Finland have been used to calculate whether HCTs improve the cost competitiveness and reduce the emissions of road transport.
The results indicate that HCTs have a 42% emission reduction potential in mass-based transport and a 38% potential in volume-based transport compared to normal semitrailers.